2018
DOI: 10.4055/cios.2018.10.1.64
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Meta-analysis of Randomized Controlled Trials Comparing Surgical versus Conservative Treatments for Acute Undisplaced or Minimally-Displaced Scaphoid Fractures

Abstract: BackgroundSurgical and conservative methods have been reported by various studies for high rates of fracture union and subsequent regain of function among patients with undisplaced or minimally-displaced scaphoid fractures. Hence, this study aims to analyze the best available evidence to comprehend the relative benefits and risks of these therapeutic options.MethodsA systematic search of the literature from different databases and search engines was performed with strict eligibility criteria to obtain the high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 22 publications
1
9
1
1
Order By: Relevance
“…The studies reported are small, with different time points, and some reviews 29 and meta-analyses have also included case series. 24,44,149,150 The data from these studies have been extracted systematically and meta-analysed on numerous occasions. [29][30][31][32][33][34]36,37 One study reported PRWE score at 10 years in 75 of 83 patients randomised to scaphoid cast treatment or surgical fixation with a Herbert headless screw and the mean score was 6 in each group.…”
Section: Sensitivity Analyses Of the Patient-rated Wrist Evaluationmentioning
confidence: 99%
“…The studies reported are small, with different time points, and some reviews 29 and meta-analyses have also included case series. 24,44,149,150 The data from these studies have been extracted systematically and meta-analysed on numerous occasions. [29][30][31][32][33][34]36,37 One study reported PRWE score at 10 years in 75 of 83 patients randomised to scaphoid cast treatment or surgical fixation with a Herbert headless screw and the mean score was 6 in each group.…”
Section: Sensitivity Analyses Of the Patient-rated Wrist Evaluationmentioning
confidence: 99%
“…Most often, athletes with a scaphoid fracture of their dominant hand are treated with surgical options for various reasons including return to play. This can be supported by a meta-analysis performed by Al-Ajmi et al which revealed that the return to work time was significantly lower (p < 0.05) among patients treated surgically [10]. In the case presented, it was decided to try non-operative treatments first with the thought that if she did not achieve adequate healing on X-ray, she would advance to surgical treatments to ensure complete healing of the fracture.…”
Section: Discussionmentioning
confidence: 86%
“…Most authors of randomized trials and meta-analyses observed that ROM and grip strength do not differ between operative and conservative groups, at 12 months or later follow-up consultations. 11,[24][25][26][27] A difference can be statistically evident at 2, 3, or 6 months follow-up favoring surgery, but not at 1 year following treatment. Outcomes remained similar even after more than 12 months of follow-up.…”
Section: Discussionmentioning
confidence: 95%